Risk factors for thyroid cancer - Ali, Amani Adel (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Thyroid cancer is the most common endocrine cancer, of which the incidence has dramatically increased worldwide in the past few decades. The most common types of thyroid cancer are papillary and follicular. These types are often curable, especially when found early. Other types include medullary, anaplastic, and Hurthle cell cancer. Most tumors of the thyroid are not cancerous. A risk factor is anything that increases a person’s chance of developing cancer. Although risk factors often influence the development of cancer, most do not directly cause cancer. Some people with several risk factors never develop cancer, while others with no known risk factors do. This report tries to give a balanced view of debated factors leading to the thyroid cancer epidemic, and to suggest potential directions in the search of modifiable risk factors to help reduce thyroid cancer.
The thyroid is a gland located in the front of the neck just below the larynx, called the voice box. A healthy thyroid gland has 2 lobes, 1 on each side of the windpipe, joined by a narrow strip of tissue called the isthmus. The thyroid is part of the endocrine system, which regulates hormones in the body. The gland absorbs iodine from the bloodstream to produce thyroid hormone. This hormone controls a person’s metabolism and is necessary for life. Thyroid cancer begins when healthy cells in the thyroid gland change, grow out of control, forming a mass called a tumor